40th annual AGU hydrology days - American Geophysical Union, author; Colorado State University, author; Colorado State University, publisher (Colorado State University. Libraries, 2020)
Includes the schedule and presentation abstracts only. The 40th Annual American Geophysical Union Hydrology Days meeting, held on April 13-14, 2020, provides a unique opportunity for students, faculty, staff and practitioners to engage in wide range of water-related interdisciplinary research topics. In addition to hydrologic systems, the event covers a broad range of water concerns, including agriculture and water rights, sustainability and conservation, climate change and urbanization, economics and policy. Hydrology Days' 40th anniversary builds on CSU legacy of excellence in water-related studies. Program includes abstracts of presentations.

Selected presentations are available in Colorado Water, vol. 37, issue 2: https://hdl.handle.net/10217/211068.
Hydrology days 2020
AGU hydrology days 2020
Due to the coronavirus (COVID-19) pandemic the 40th annual American Geophysical Union hydrology days in-person meeting was canceled to protect public health and safety. The organizing committee is committed to sharing knowledge and ideas throughout our strong and vibrant scientific community. Therefore, the event was moved to voluntary online presentations to provide an opportunity for students and scientists to share their research. Conference proceedings for the webinar have been published in recognition of the hard work and outstanding efforts of our community.
Keywords: Hydrology -- Congresses